2009
DOI: 10.1177/0363546509332498
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Reconstruction of the Medial Collateral Ligament and Posteromedial Corner of the Knee in Patients With Chronic Medial Collateral Ligament Instability

Abstract: Acceptable clinical results with the MCL reconstruction technique were achieved in patients suffering from chronic valgus instability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
246
2
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(266 citation statements)
references
References 23 publications
11
246
2
7
Order By: Relevance
“…We observed no limitation in the ROM in our patients with proximal repair, while, in MCL reconstructions, Lind et al [13] found ROM deficits in 20% of patients. The mini-invasive technique, associated with BPTB ACL reconstruction, restored the medial laxity not addressed by an isolated ACL reconstruction [32] and preserved the active medial restraints, which surgeons frequently use in reconstructive techniques.…”
Section: Discussioncontrasting
confidence: 46%
See 2 more Smart Citations
“…We observed no limitation in the ROM in our patients with proximal repair, while, in MCL reconstructions, Lind et al [13] found ROM deficits in 20% of patients. The mini-invasive technique, associated with BPTB ACL reconstruction, restored the medial laxity not addressed by an isolated ACL reconstruction [32] and preserved the active medial restraints, which surgeons frequently use in reconstructive techniques.…”
Section: Discussioncontrasting
confidence: 46%
“…The medial collateral ligament (MCL) is the most frequently injured ligament in the knee [13]. Most MCL lesions heal with nonoperative treatment and chronic MCL instability is rare [18], but up to 78% of Grade III MCL injuries are associated with an ACL lesion [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the majority of previously described techniques are more slingtype procedures [2,7,10] and do not reproduce the native anatomy of the medial knee, the ability to initiate early knee motion is compromised. Similar to the reconstruction history of the cruciate ligaments and the posterolateral aspect of the knee, over time, surgeons have strived to develop more anatomic reconstructions over sling procedures due to improved outcomes with more objective measurement techniques.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] When autograft was used for MCL reconstruction, the semitendinosus was the exclusive autologous graft choice described. [5][6][7] The disadvantages of using allografts for reconstructing the knee ligaments relate to financial costs, 8 concerns regarding tissue quality with slower biological incorporation, 9 disease transmission, 10 and some evidence of higher failure rates and inferior functional outcomes in young active adults, at least for the ACL. 11 The potential disadvantages of using autologous hamstring for reconstructing the MCL in the ACL-deficient knee include weakening of the hamstring's anterior restraining action.…”
mentioning
confidence: 99%